Penanaman Nilai-Nilai Toleransi Beragama Melalui Pembelajaran Tematik - Mochamad Farouk (Ambarsa : Jurnal Pendidikan Islam, 2023)
Tolerance is mutual respect regardless of ethnicity, gender, appearance, culture, beliefs, abilities, or sexual orientation. People who are tolerant can respect others despite different views and beliefs. In the context of tolerance, people cannot tolerate cruelty, bigotry, and racism. Therefore, with this tolerance, people can make the world a humane and peaceful place. In this case related to tolerance is an attitude that does not deviate from the rules, where someone respects or respects every action that others do. In the socio-cultural and religious context, tolerance can be interpreted as attitudes and actions that prohibit discrimination against different groups or cannot be accepted by the majority in a society. This paper intends to describe: 1. Religious Tolerance Values 2. Thematic Learning 3. Planting Religious Tolerance Values Through Thematic Learning. The conclusion is that tolerance is mutual respect regardless of ethnicity, gender, appearance, culture, beliefs, abilities, or sexual orientation. People who are tolerant can respect others despite different views and beliefs. In the context of tolerance, people cannot tolerate cruelty, bigotry, and racism. Therefore, with this attitude of tolerance people can turn the world into a humane and peaceful place, thematic learning is one of the integrated learning models. Thematic learning is one type of integrated learning, where the integrated curriculum is the parent. Thematic learning places more emphasis on student involvement. active students in the learning process, both in seeking knowledge and solving problems. Thematic learning is not solely for students to know (learning to know), but students must do (leraning to do), to be (learning to be), and to live together (learning to live together). Learning places more emphasis on enjoyable learning, without pressure and fear. In accordance with the steps of the thematic learning in terms of planning the teacher must identify themes related to religious tolerance in Madrasah Ibtidayah from lower to upper levels, after the theme is identified next teacher assignment is to arrange the steps of thematic learning to be directed. In detail the steps of the thematic learning are as follows.